Modelo de gestión en la calidad de servicio mediante la Normativa ISO 9001: 2015 para el Hostal Café Tiana. - Pacheco Cueva, Cristhian Alexis (2021)
This research focused on design a quality management model through the ISO 9001: 2015 standard, which aims to strengthen the quality of service in the Hostel Café Tiana due to the scant planning and little follow-up to the client. Through a quantitative, inductive where deductive methodology. For the realization of this work, three main stages were taken into account, the first one and, important concepts of the investigation were based theoretically, the description of investigations similar to the subject, the evolution of the pertinent concepts over time. The second stage consisted of the diagnosis, information was collected through the use of SWOT, checklist, and personnel interviews. On the other hand, the realization of the proposal, an adequate management model was designed in the ISO 9001: 2015 standard, which includes the general situation of the organization, institutional values, internal evaluation, identification of interested parties, quality policy, strategies, map of processes, design of procedures and job profiles, in addition to their functions. The last stage is the validation of said proposal delivered by experts in the field, where its analysis and the evaluation of the work carried out are described.